PELANGGARAN WISATAWAN TERHADAP PERATURAN PENGUNJUNG DI CANDI BOROBUDUR - Aan Wahyu Lestari; Diananta Pramitasari; Ahmad Saifullah MJ (Magister Tourism Study, Faculty of Tourism, Udayana University, 2018)
Visitor Code of Conduct is an effort to minimize negative impact caused by tourist visitation to the Borobudur Temple. It have been applied since 2010 and socialized to the tourists by regulatory boards, security officers and guides. However, there are still tourist violations towards it. This research aims to describe the characteristics of tourist violation towards Visitor Code of Conduct and to find out the causative factors of the tourist violation towards Visitor Code of Conduct. The data was collected by observation, interview and questionnaire, and analysed by descriptive analysis. The results of the research are: 1) the most violator towards Visitor Code of Conduct are male, 17-24 years old, well educated, from outside Java, repeater, visiting for recreation, with friends or family, with most violations is related to stupas (73.8%) 2) factor of motive, knowledge of the Visitor Code of Conduct, knowledge of the violation’s impact and enforcement of regulation has caused tourists to commit violation, while attitudes toward Visitor Code of Conduct and environment cues do not cause tourists violation.